PRIMEIRO REGISTRO DE Schizophragma bicolor (DOZIER, 1932) (HYMENOPTERA: MYMARIDAE) NO BRASIL - Santos, Rodrigo Souza; Costa, Valmir Antonio (REVISTA DE AGRICULTURA, 2015)
PRIMEIRO REGISTRO DE Schizophragma bicolor (DOZIER, 1932) (HYMENOPTERA: MYMARIDAE) NO BRASIL